Nursing Care for Mr. W Diagnosed with Hemorrhoids in the Kemuning Ward of Waled Hospital in Cirebon Regency - Kiki Ameliya; Erida Fadila; Dewi Oktoviani; Evi Nurmala Fia; Rizal Nova Jalaludin (Al Makki Publisher, 2024)
Hemorrhoids are dilated blood vessels in the anus that originate from the hemorrhoidal plexus, which will cause discomfort resulting in swelling commonly called hemorrhoids or hemorrhoids. The purpose of this study was to describe the identification of nursing care in patients with a medical diagnosis of hemorrhoids in the Kemuning room of Waled Hospital, Cirebon Regency. This research method is a qualitative descriptive research conducted at Waled Hospital. Data was collected through observation, interviews, and medical record documentation studies. The main focus of the research is on the nursing problems that arise, such as acute pain, and the interventions provided, such as relaxation techniques. The results showed that relaxation techniques are one of the effective interventions in reducing acute pain in patients with hemorrhoids. Before the intervention, patients often experience pain with a scale level of 5, which is shown by grimacing expressions. However, after doing relaxation therapy, the patient's pain scale decreased to 3, and the patient's expression seemed calmer. This study implies that non-pharmacological techniques such as relaxation can be a practical companion to pharmacological therapy in pain management in hemorrhoidal patients. Emphasis on holistic and individualized nursing care is essential in improving the quality of care for patients with this medical condition.